Analysis of Risk Factors Associated with Maternal Mortality for the Period of 2022-2023 in City X - Ariati, Haji; Noor, Meitria Syahadatina; Sanyoto, Didik Dwi; Al Audhah, Nelly; Musafaah, Musafaah (Journal La Medihealtico, 2024)
Maternal mortality rate as an indicator of The maternal mortality rate is an indicator of the nation's health status and a component of the development index and quality of life for a long time. MMR in South Kalimantan in 2023 was recorded as 145 deaths per 100,000 KH. X is the city that has the highest MMR in the last two years, namely 131 per 1000,000 KH in 2022 and 131 per 1000,000 KH in 2022 and 145 per 100,000 KH in 2023. To determine the relationship between age, parity, medical history, education level, income, family support and mortality, education, income, family support with maternal mortality in the period 2022-2023 in X City. This study used a case control design. The research subjects consisted of 87 respondents in the working area of the X City Health Office. X city. Data analysis chi square test and multiple logistic regression test. The results of the study The results showed that the most dominant variables associated with maternal mortality in X City is the most dominant in sequentially starting from the most dominant is the history of disease (10.234), age (7.757), parity (6.327), family support (4.874), income (1.309), and education level (1.206). (1,206). There is an association between age, parity, history of illness, and, family support but no association of education level and income with maternal mortality for the period 2022-2023 in X City.